CONSUMPTION OF ENERGY DRINKS AND THEIR SHORT-TERM HEALTH EFFECTS ON CHILDREN IN IRAQ: A CROSS-SECTIONAL STUDY - Noaman, Aqeel Abbas (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2025)
Background: Energy drinks are non-alcoholic beverages that contain more sugar and caffeine, along with many energy-enhancing ingredients. This type of drinks is very popular among Iraqi adolescents although it may cause negative effect on health. Purpose: To determine the prevalence of energy drink consumption and its effects on some health aspects among children between the ages of 6 and 15 years. Methods: A cross-sectional study was carried out on a random sample of 548 primary and middle school children aged 6–15 years from four main schools in the village of Zuhairat/Diyala Governorate for the period from December 10, 2020, to January 22, 2021. We statistically analyzed the data using SPSS, version 21.0. A binary logistic regression analysis was used for short-term health effects in relation to energy drink consumption; a p-value of 0.05 was used as the lowest limit for statistical significance. Results: The study shows that the prevalence of energy drink consumption among children aged 6–15 years was estimated at 20.4%. Significantly, 76.8% of children had energy drinks once a week. Younger children significantly had 62.4% lower odds of daily consuming energy drinks than older children (OR = 0.376, CI: 0.237-0.598, p = 0.000). The majority of children who consumed energy drinks daily significantly had a poorer appetite than those who did not (72.3% vs. 55.3%, p = 0.001), (OR = 0.473; CI: 0.300-0.745). Conclusion: Most children who reported consuming energy drinks daily had a significantly poorer appetite and fewer sleep hours than those who did not.